Photophysical Encapsulation and Release of Acridine Orange Confined In Graphene-Oxide Mediated Bile-Salt Aggregates - Gujral, Jaideep (My University, 2019)
In the present work, Acridine Orange, a cationic fluorescent dye has been made to interact with three different bile-salt aggregates (NaC, NaDC and NaTC). The photophysical studies of AO have been carried out by varying the concentrations of different bile salts in the presence/absence of Graphene Oxide. An important aim of the present thesis is to extensively study the UV and the fluorescence properties of AO-BileSalt-GO and AO-GO-BileSalt systems. In PBS medium, AO molecule exhibits fluorescence at exi= 465 nm and exi= 490 nm. It has been observed from the UV and fluorescence studies that AO shows ambiguous behavior with different bile salts. GO acts as a quencher generally, and thus leads to the decrease in the fluorescence and UV absorbance values. In AO-BileSalt-GO system, the fluorescence and UV absorbance values of AO increase on addition of the different bile salts. On further addition of GO in the system resulted in the decrease in the fluorescence and absorbance values. This has also been confirmed by calculating the fluorescence quantum yield by using Quinine Sulphate as the standard. Moreover, the binding constant results confirm the phenomenon. For the reverse system, i.e. AO-GO-BileSalt, the fluorescence and UV absorbance values of AO decreases on addition of GO. On addition of BileSalt to this system leads to the increase in fluorescence and absorbance values. The results have been verified by calculating the fluorescence quantam yield and binding constant. The results suggest that AO molecules get entrapped in the bile salt aggregates. While the addition of GO in all the three bile-salt systems results quenching of absorption, fluorescence emission and quantum yield values. Moreover, in presence of GO, the studied fluorophore (AO) releases from the encapsulated bile-salt complexes to the aqueous medium of GO.
Keywords: bile salt; ao; go; Nac; NaDc